Learning Educational Values from Harry Potter Character - Iswanda Meiliestya Pradini; I.G.A Lokita Purnamika Utami; Gede Mahendrayana (English Teaching Journal : A Journal of English Literature, Language and Education, 2021)
Implementing a good character education from an early age will form a qualified personality for children. Societies use novels in embedding the value of character education. This research aimed to analyze the characterization of Harry Potter in a novel entitled “Harry Potter and the Deathly Hallows”. The character was analysed based on five core values of character education proposed by the Ministry of Education and Culture of Indonesia; religious, nationalist, independent, mutual cooperation, & integrity. This research was conducted in descriptive qualitative research design. The data collection technique used were close reading and note taking. The obtained information were analyzed through textual analysis. Data triangulation, theory triangulation, and investigator triangulation were used to check the trustworthiness of the data. The findings showed that Harry Potter had 20 characterizations and 11 values of character education which were portrayed through the action, speech, and direct description by the author in the story. Relating to the context of Indonesian’s character building used as a research foundation, some identified characterizations have occupied the five cores values mentioned. The religious and mutual cooperation values were more emphasized in the whole story. Implication related to the use of this finding as a future learning-material was provided